The use of whey protein extract for manufacture of a whipped frozen dairy dessert - Olga Musina; Ali Rashidinejad; Predrag Putnik; Francisco J. Barba; Alireza Abbaspourrad; Ralf Greiner; Shahin Roohinejad (Mljekarstvo)
The aim of this work was to substantiate the use of whey protein extract (WPE), a by-product of dairy industry, combined with different berry purees in the formulation of a whipped frozen dairy dessert (WFDD). After freezing, the swelling ability of WPE decreased significantly while at higher temperatures of the dispersion medium, the degree of swelling increased. A mixture containing 55±2 % WPE and 45±2 % milk presented a homogeneous consistency while the further processing did not improve the structure of the mixture. Final formulations of WFDD containing different berry purees (i.e. 10 % black¬currant puree, 25 % cherry puree, or 30 % strawberry puree) were proposed for which the nutritional facts were calculated. Recommended shelf life of the developed desserts at -18 °C is suggested to be 20 days. Regulatory requirements and recommendations for the production of WFDD in an industrial scale were also developed. Recommended shelf life of the developed desserts at -18 °C is suggested to be 20 days. In conclusion, a WFDD was developed using WPE as a by-product of dairy industry.